Prosiding Seminar Nasional Fisika (E-Journal) Snf2018 Unj 2018
DOI: 10.21009/03.snf2018.01.pe.02
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Ensiklopedia Alat Optik Berbasis Problem Based Learning

Abstract: Penelitian ini bertujuan untuk mengembangkan ensiklopedia alat optik berbasis problem based learning. Jenis penelitian yang digunakan adalah penelitian pengembangan (R&D) dengan model pengembangan ADDIE (Analysis, Design, Development, Implement, Evaluation). Penelitian dilakukan di Laboratorium fisika FMIPA UNJ. Ensiklopedia yang dikembangkan ini dilengkapi dengan model pembelajaran yang sesuai dengan karakteristik materi alat optik. Ensiklopedia telah divalidasi oleh ahli, yaitu ahli materi, ahli media, dan a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The percentage of score obtained is then measured using the score interpration for the Likert scale [14]. To be able to find out the response of users to develop IoT-based garbage collection robots, you can see from the likert scale table.…”
Section: E Testing and Resultsmentioning
confidence: 99%
“…The percentage of score obtained is then measured using the score interpration for the Likert scale [14]. To be able to find out the response of users to develop IoT-based garbage collection robots, you can see from the likert scale table.…”
Section: E Testing and Resultsmentioning
confidence: 99%
“…Based on the results of the questionnaire provided, it can be concluded that students are less interested or less interested in carrying out reading activities at school, so teachers encounter obstacles in the form of developing interesting reading materials to improve students' literacy skills. Based on the initial research and gathering of information, interesting reading materials based on local Pakpak culture are needed for class X students at SMA Negeri 1 Sidikalang.The research process was carried out based on the research and development stage which was adapted from the Bord and Gall model, namely (1) information collection was carried out with 2 steps of analysis, namely problem analysis and needs analysis carried out by researchers with observation, interviews, and distributing questionnaires; (2) product planning, (3) initial product in the form of explanatory text teaching materials assisted by digital photo sheet (scrapbook) media, (4) validation in terms of material/content and design by 4 validators,(5) product revision or improvement based on suggestions validator, (6) initial trials conducted in three stages, namely individual trials of 5 students, small group trials of 10 students, and limited field trials of 35 students, (7) revisions or product improvement, (8) conducting operational field trials, and (9) revising or repairing if necessary. Several stages of the research become guidelines for producing reading materials that can be used according to the needs of teachers and students as users.…”
mentioning
confidence: 99%